The effect of oral zonisamide treatment on serum phenobarbital concentrations in epileptic dogs - Mahon, Elizabeth; Marsh, Oliver; Uriarte, Ane; Stabile, Fabio (Frontiers in Veterinary Science, 2024)
Zonisamide is used in dogs for the treatment of epileptic seizures. It is predominantly metabolised by CYP450 hepatic enzymes. When used concurrently with phenobarbital, zonisamide clearance is increased and its elimination half-life decreases. However, the effect that zonisamide may have on phenobarbital serum concentrations in dogs has not been previously described. Eight dogs diagnosed with idiopathic epilepsy and two dogs with structural epilepsy commenced zonisamide at 8.0mg/kg/12h [7.4-10mg/kg/12h] following an increase in epileptic seizure frequency. Nine dogs were receiving PB every 12 hours (4.2mg/kg/12h [3.8-6mg/kg/12h]), and one dog was receiving PB every 8 hours (6mg/kg/8h).Following addition of zonisamide and despite no increase in phenobarbital dosage, 9/10 dogs had increases in phenobarbital serum concentrations in subsequent measurements. In five dogs phenobarbital serum concentrations were increased to concentrations above the reported hepatotoxic concentrations (trough>35mg/L). This required a reduction in phenobarbital daily doses. This case series suggests that zonisamide affects the metabolism of phenobarbital and causes an increase in phenobarbital serum concentrations over time.